2007
DOI: 10.1002/hyp.6524
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Turkish precipitation data: homogeneity and the Southern Oscillation forcings on frequency distributions

Abstract: Abstract:The homogeneity of newly compiled 212 precipitation records in Turkey for the period 1973-2002 was checked by the Standard Normal Homogeneity Test (SNHT) and Pettitt Test. Stations were considered inhomogeneous if at least one of the tests rejects the homogeneity. As a result, 43 out of 212 stations were found to be inhomogeneous. In addition, the previously detected Southern Oscillation (SO)-related precipitation anomalies by the authors were quantified at each station using the gamma distribution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The results of methods showed that 43 out of 212 stations had an inhomogeneity. The comparison of the results of this study and the paper presented by Karabörk et al (2007) shows that the stations for which the homogeneity is deteriorated are similar. In both the studies the inhomogeneity was detected at stations 17026, 17606 and 17648 located in northern Turkey.…”
Section: Homogeneity Testmentioning
confidence: 56%
See 2 more Smart Citations
“…The results of methods showed that 43 out of 212 stations had an inhomogeneity. The comparison of the results of this study and the paper presented by Karabörk et al (2007) shows that the stations for which the homogeneity is deteriorated are similar. In both the studies the inhomogeneity was detected at stations 17026, 17606 and 17648 located in northern Turkey.…”
Section: Homogeneity Testmentioning
confidence: 56%
“…There are many methods proposed and applied for testing homogeneity of meteorological series. The methods for testing the homogeneity of the series may be classified into two groups as 'absolute method' and 'relative method' (Karabörk et al 2007). In the first method, the test is applied for each station individually.…”
Section: Homogeneity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pettitt test, which has been used for studying homogeneity of hydro-meteorological datasets (Karabörk et al, 2007;Hakuba et al, 2013;Xie ., 2014), is applied to detect change points. The Pettitt test, which has been used for studying homogeneity of hydro-meteorological datasets (Karabörk et al, 2007;Hakuba et al, 2013;Xie ., 2014), is applied to detect change points.…”
Section: Methodsmentioning
confidence: 99%
“…Karabork et al, (2007) analyzed the homogeneity of precipitation data of 212 stations in Turkey belonging to 1973-2002, using the SNH and Pettitt tests. They expressed that the 43 out of 212 stations were impacted from non-climatic conditions resulting in inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%